2023
DOI: 10.1021/acs.est.2c07969
|View full text |Cite
|
Sign up to set email alerts
|

PFAS-Contaminated Soil Site in Germany: Nontarget Screening before and after Direct TOP Assay by Kendrick Mass Defect and FindPFΔS

Abstract: Soil contaminations with per-and polyfluoroalkyl substances (PFAS) are of great concern due to their persistence, leading to continuous, long-term groundwater contamination. A composite sample from contaminated agricultural soil from northwestern Germany (Brilon-Scharfenberg, North Rhine-Westphalia) was investigated in depth with nontarget screening (NTS) (Kendrick mass defect and MS 2 fragment mass differences with FindPFΔS). Several years ago, selected PFCAs and PFSAs were identified on this site by detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“… 5 , 6 , 36 Previous studies also identified other PFAS transformation patterns under HO • oxidation, such as the exclusive formation of C 7 F 15 –COO – from C 8 F 17 –SO 2 NH 2 15 and the dominating formation of – OOC–C n –1 F 2 n –2 –COO – from H–CF 2 –C n –1 F 2 n –2 –COO – ( Figure 2 d). 18 We recommend (i) pretreating the samples with both HO • and SO 4 – • (and sequential treatment, if needed) before target PFAS analysis, (ii) adding more known structures (e.g., – OOC–C n F 2 n –COO – , ether carboxylates/sulfonates, and other commercially available PFAS chemicals) to the target list of TOP assay, (iii) using advanced mass spectrometry methodologies, 37 data processing algorithms, 38 and additional spectroscopy methods (e.g., 19 F NMR) to assist structural determination, and (iv) modifying the existing methodologies with new structural transformation mechanisms. In order to satisfy the imminent need for the detection, monitoring, and treatment of “non-legacy” PFAS pollutants, it is imperative to expand our understanding of structure-transformation relationships for emerging PFAS chemicals.…”
Section: Resultsmentioning
confidence: 99%
“… 5 , 6 , 36 Previous studies also identified other PFAS transformation patterns under HO • oxidation, such as the exclusive formation of C 7 F 15 –COO – from C 8 F 17 –SO 2 NH 2 15 and the dominating formation of – OOC–C n –1 F 2 n –2 –COO – from H–CF 2 –C n –1 F 2 n –2 –COO – ( Figure 2 d). 18 We recommend (i) pretreating the samples with both HO • and SO 4 – • (and sequential treatment, if needed) before target PFAS analysis, (ii) adding more known structures (e.g., – OOC–C n F 2 n –COO – , ether carboxylates/sulfonates, and other commercially available PFAS chemicals) to the target list of TOP assay, (iii) using advanced mass spectrometry methodologies, 37 data processing algorithms, 38 and additional spectroscopy methods (e.g., 19 F NMR) to assist structural determination, and (iv) modifying the existing methodologies with new structural transformation mechanisms. In order to satisfy the imminent need for the detection, monitoring, and treatment of “non-legacy” PFAS pollutants, it is imperative to expand our understanding of structure-transformation relationships for emerging PFAS chemicals.…”
Section: Resultsmentioning
confidence: 99%
“…So far, through the combination of different screening strategies, the identification of novel PFAS in the environment can be achieved accurately and efficiently. ,, Nevertheless, with the TOP assay embedded in the strategy of nontarget analysis, not only novel PFAS can be identified but also their potential roles in the environmental processes can be predicted. Previously, novel products such as HPFCAs, UPFECAs, and perfluoroalkyl diacids were identified as possible transformation products of other PFAS. , However, the identification of potential transformable precursors, especially those weakly ionized and semivolatile PFAS, are challenging due to their low deprotonation capability in electrospray-ionization-based MS/MS analysis. In this study, three per-/polyfluorinated alcohols were successfully identified as either precursors or products with the embedded TOP assay, probably favored by their high levels in the soils from the oil refinery.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Suspect and homologue-based nontarget screenings were initially applied and identified 40 classes of PFAS in AFFFs and AFFF-impacted groundwater in 2017 . More recently, fragment-based nontarget screening has proven to be an efficient strategy. A combination of the three screening strategies was also applied in Chinese municipal wastewater treatment plants and newly identified 12 PFAS, including 3:1 H-substituted perfluoroalkyl ether carboxylic acid (H-PFECA) and 1: n ( n = 2, 3) perfluoroalkyl ether alcohol (PFEA) . However, only a few studies have embedded the TOP assay in HRMS-based nontarget analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is motivated by the sheer chemical diversity available to the PFAS family and the urgency to understand and prioritize risk assessment of these ubiquitous pollutants. Since the emergence of fluorinated alternatives, including (1) shorter-chain homologues of legacy PFAS, (2) functionalized polyfluoropolyethers (PFPEs), and (3) sulfonic/phosphoric acids, very few studies have reported their physicochemical, bioaccumulative, toxicological, or biotransformative properties. , Additionally, precursor compounds are on the radar as potentially unaccounted-for sources of PFAS exposure. Little information is readily available on any of the pertinent properties for these emerging in pollutants …”
Section: Introductionmentioning
confidence: 99%